Peningkatan Pemahaman Profil Pelajar Pancasila Terhadap Guru IPS Tingkat SMP Se-Kota Parepare dalam Implementasi Kurikulum Merdeka - Masita; Marwati Abd. Malik; Melinda; Musrifah; Nur Izzatil Hasanah; Nurjaya Syamsualam; Nurserianti; Nurul Fadhilah; Riska Amelia Insani Bakri; Mas’ud Badolo (Faculty of Tarbiyah and Teacher Training, 2024)
Indonesian students need to possess the qualities and skills outlined in the Pancasila Student Profile (P3) in order to succeed in the classroom and in society after graduation. There are still problems with the Pancasila Student Profile implementation process, such as teachers' not being competence to interpret P3 in relation to it. Teachers still struggle to determine when P3 should be implemented, and they don't seem creative when it comes to making a project to the unique needs of the chosen students. They also seem to believe that all projects must result in a finished output. The goal of the project seminar, which is a type of community service activity, is to help social studies teachers in the city of Parepare understand how to use Pancasila students (p5) in the classroom as a way to develop students' character. The seminar is focused on raising the profile of Pancasila students (p5) in the junior high school level in the social studies field. Observing teacher needs through surveys and interviews, planning, and seminar execution are the first steps in the implementation process employed for this community activity. The findings of the questionnaires completed by seminar attendees after the activity are used to assess the degree of success of the service. According to the computations from the questionnaire, 93,86% of respondents fell into the very good category. The results of this evaluation indicate that the activities carried out were able to increase teachers' knowledge regarding P3, increase understanding in implementing P3, and motivate teachers to implement P3 in schools well. As a result, it is strongly advised that service projects be conducted often to help teachers become more successful at applying the Pancasila student profile.